Study of simply connected convex domain and its geometric properties (II). Issue 1 (11th December 2019) - Faisal, M. I.
Abstract : In this paper, making use of a new integral operator defined in the open unit disk we introduce and study a new class of simply connected convex domain of analytic and univalent functions. We derive some inclusion results and its geometric properties. Moreover, we discuss analytic criteria for a member of the simply connected convex domain to be a member of the class of functions with positive real part greater than μ .